2010
DOI: 10.1186/1742-2094-7-76
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A is increased in the serum and in spinal cord CD8 and mast cells of ALS patients

Abstract: The contribution of inflammation to neurodegenerative diseases is increasingly recognized, but the role of inflammation in sporadic amyotrophic lateral sclerosis (sALS) is not well understood and no animal model is available. We used enzyme-linked immunosorbent assays (ELISAs) to measure the cytokine interleukin-17A (IL-17A) in the serum of ALS patients (n = 32; 28 sporadic ALS (sALS) and 4 familial ALS (fALS)) and control subjects (n = 14; 10 healthy subjects and 4 with autoimmune disorders). IL-17A serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 48 publications
6
122
4
Order By: Relevance
“…Most importantly, many of these immune changes in the animal model have been confirmed in patients with nonhereditary ALS [24,70,99,100,131,132]. Henkel et al [133] demonstrated that in patients with rapidly progressing clinical states, an inverse correlation was seen between Treg numbers in the blood and leukocyte levels of FoxP3, a transcription factor required for Treg suppressive function [134].…”
Section: Neuroinflammation In Patients With Als: Tregsmentioning
confidence: 98%
See 1 more Smart Citation
“…Most importantly, many of these immune changes in the animal model have been confirmed in patients with nonhereditary ALS [24,70,99,100,131,132]. Henkel et al [133] demonstrated that in patients with rapidly progressing clinical states, an inverse correlation was seen between Treg numbers in the blood and leukocyte levels of FoxP3, a transcription factor required for Treg suppressive function [134].…”
Section: Neuroinflammation In Patients With Als: Tregsmentioning
confidence: 98%
“…Understanding the role of Tregs play in neurodegeneration has spread, encompassing many different neurodegenerative diseases, including ALS [51,98]. The role of Th17 is less well defined in the mSOD1 transgenic animal, but evidence from patients with ALS supports their involvement in the neuroinflammatory process [98][99][100][101].…”
Section: T Lymphocytesmentioning
confidence: 99%
“…[59] Th17 cells are crucial for the development of certain autoimmune diseases, exhibiting neurodestructive effects in neuroinflammatory diseases. [60] In ALS patients, elevated IL-17 and Th17-related cytokines (IL-6, TNF-α, IL-1 and IL-23) [61][62][63] have been observed. However, the contribution of Th17 cells in promoting ALS development has not been established yet because of two challenges: late diagnosis and chronic disease.…”
Section: Th17 Cells Nerve Injury and Alsmentioning
confidence: 99%
“…The main histopathological feature of inflammation is the proliferation of reactive astrogliosis and of activated microglial cells, associated with alterations in their cellular functions, such as glutamate reuptake failure and release of proapoptotic and proinflammatory factors (Sanagi et al, 2010;Sargsyan et al, 2005;Sofroniew, 2005). Molecules associated with inflammatory process, such as interleukins 6, 12, 15, 17A, 23, C4d and C3d complement proteins, as well as tumor necrosis factor-alpha, have been found in blood and CSF from ALS patients (Almer et al, 2002;Fiala et al, 2010;Henkel et al, 2004;Kawamata et al, 1992;McGeer et al, 1991;Moreau et al, 2005;Rentzos et al, 2010a, b). The finding of increased levels of granzymes A, B in serum (Ilzecka, 2011) and decrease in cytochrome c levels in the CSF (Ilzecka, 2007), suggests an apoptotic process in human disease.…”
Section: Inflammationmentioning
confidence: 99%